Arundic Acid Prevents Developmental Upregulation of S100B Expression and Inhibits Enteric Glial Development - Hao, Marlene M.; Capoccia, Elena; Cirillo, Carla; Boesmans, Werend; Vanden Berghe, Pieter (Frontiers in Cellular Neuroscience, 2017)
S100B is expressed in various types of glial cells and is involved in regulating many aspects of their function. However, little is known about its role during nervous system development. In this study, we investigated the effect of inhibiting the onset of S100B synthesis in the development of the enteric nervous system (ENS), a network of neurons and glia located in the wall of the gut that is vital for control of gastrointestinal function. Intact gut explants were taken from embryonic day (E)13.5 mice, the day before the first immunohistochemical detection of S100B, and cultured in the presence of arundic acid, an inhibitor of S100B synthesis, for 48 hours. The effects on Sox10-immunoreactive enteric neural crest progenitors and Hu-immunoreactive enteric neurons were then analysed. Culture in arundic acid reduced the proportion of Sox10+ cells and decreased cell proliferation. There was no change in the density of Hu+ enteric neurons, however, a small population of cells exhibited atypical co-expression of both Sox10 and Hu, which was not observed in control cultures. Addition of exogenous S100B to the cultures did not change Sox10+ cell numbers. Overall, our data suggest that cell-intrinsic intracellular S100B is important for maintaining Sox10 and proliferation of the developing enteric glial lineage.